Recurrent dermatofibrosarcoma protuberans of the breast: A case report and review of literature - P, Monica; Narayan, Geeta S; Kumar, BR Kiran (Indian Journal of Case Reports, 2024)
Dermatofibrosarcoma protuberans (DFSP) is a rare and low-grade sarcoma of fibroblast origin with a tendency to invade and recur locally. The most common sites of origin of DFSP are the head, neck, and extremities. However, DFSP breast has also been reported. It infiltrates surrounding subcutaneous tissue and fascia, with an incidence of